Requirements for Employing Augmented Reality Technology in Blended Learning Environment by Female English Teachers in the Light of Innovations Dissemination Theory - Alharthi, Fatima Saleh; Hassan, Hala Ibrahim (Journal of Educational and Psychological Sciences, 2023)
The research aimed at identifying the requirements for employing Augmented Reality technology in blended learning environment for teaching English in the light of Innovations Dissemination Theory, from female teachers’ point of views. The researcher used Survey Descriptive Approach. The study sample consisted of (102) female English teachers in Bisha Governorate, school year 1443/ 2022. For data collection, the research instrument was a questionnaire. The study concluded to a set of findings including: The responses of English language teachers to the stages of using augmented reality technology in blended learning environment for teaching English in the light of Innovation Dissemination theory was at a significant consent degree. The human requirements for employing Augmented Reality technology were at medium degree. The educational and administrative requirements were at significant degree of consent. In the light of the findings, the study recommended to: develop English curricula, inclusion and setting courses contents to be implemented using (AR) technology. Holding workshops for English female teachers; for adopting culture of (AR) in teaching; thus, it will impact on students and increasing outcomes of educational process.
Keywords: Augmented Reality; blended learning; Innovations Dissemination Theory